1995
DOI: 10.1037/0022-0167.42.2.232
|View full text |Cite
|
Sign up to set email alerts
|

Measuring belongingness: The Social Connectedness and the Social Assurance scales.

Abstract: The study developed 2 measures of belongingness based on H. Kohut's (1984) self psychology theory. The Social Connectedness Scale and the Social Assurance Scale were constructed with a split-sample procedure on 626 college students. Internal reliability estimates for the 2 scales were .91 and .82, respectively. Test-retest correlations revealed good test stability over a 2-week period (rs = .96 and .84, respectively). Cross-validation for the 2 measures was achieved with confirmatory factor analysis with an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
908
3
33

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 977 publications
(962 citation statements)
references
References 57 publications
18
908
3
33
Order By: Relevance
“…In research pertaining to the measurement of belonging, Lee and Robbins (1995) propose that the notion of belongingness is composed of three main constructscompanionship, affiliation and connectedness. While companionship is the act of bonding with another human being and affiliation is the establishment of peer relations of similar values, connectedness is a feeling of relatedness and identification of differences.…”
Section: Connectednessmentioning
confidence: 99%
See 1 more Smart Citation
“…In research pertaining to the measurement of belonging, Lee and Robbins (1995) propose that the notion of belongingness is composed of three main constructscompanionship, affiliation and connectedness. While companionship is the act of bonding with another human being and affiliation is the establishment of peer relations of similar values, connectedness is a feeling of relatedness and identification of differences.…”
Section: Connectednessmentioning
confidence: 99%
“…In a study of the social connectedness in university settings, Lee and colleagues (Lee, Keough, & Sexton, 2002) modified the original Social Connectedness Scale (Lee & Robbins, 1995) to study interpersonal closeness and factors that influence perceptions of closeness. The study found that women who experience low connectedness reported a negative campus climate and higher level of stress.…”
Section: Connectednessmentioning
confidence: 99%
“…Measures of social functioning included a 3-item modified version of the UCLA Loneliness Scale [43] and a 3-item modified version of the Social Connectedness Scale [44]. Both of these measures ask about frequency of feeling socially isolated and alone ("never" to "very often").…”
Section: Social Functioning and Life Outlookmentioning
confidence: 99%
“…Adolescence is regarded as a critical period in terms of social connectedness (55,62) and technological addictions such as internet addiction, social media addiction, digital game addiction and smartphone addiction (4,15,22). The use of technologies such as the internet and social media is more common among adolescents.…”
Section: Introductionmentioning
confidence: 99%